Luteinizing hormone supplementation in controlled ovarian stimulation: the Iran Delphi consensus - Salehpour, Saghar; Aleyasin, Ashraf; Moini, Ashraf; Mousavifar, Nezhat; Mohammadhossein, Nasresfahani; Abdollahi Fard, Sedighe; Marzie, Sanuiefarimani; Mohammadzadeh, Mahboubeh; Fischer, Robert (Frontiers in Reproductive Health, 2024)
Numerous consensus documents worldwide address luteinizing hormone (LH) supplementation in controlled ovarian stimulation, yet to the best of our knowledge, only one consensus paper has been published in the Arab region. This study presents a Delphi consensus by seven Iranian infertility experts, offering real-world clinical perspectives. The aim was to develop evidence-based opinions on LH's role alongside FSH in various aspects of assisted reproductive technology (ART), including LH levels, monitoring, r-hLH use, and suggested activity. Employing the Delphi consensus approach, the Iran consensus unfolded in three steps. In Step 1, eight out of 10 statements gained approval, while two unclear statements were removed. In Step 2, the 20-member extended panel voted on the remaining eight statements; only one (statement 3) lacked consensus (55% agreement), prompting a modification. The revised statement (noted as statement 3') obtained an 83% agreement. The clinical perspectives included in this consensus complement clinical guidelines and policies that help further improve treatment outcomes, especially for patients with FSH and LH deficiencies.